Práticas corporais na comunidade tradicional Alto Santa Maria : continuidades e descontinuidades - Santos, Milainy Ludmila (2014)
The aim of this study was to identify games and playful activities, dances as well as other corporal practices in order to analyse the process in which they are learned by individuals in the dynamics of social relations inside communities. More specifically, the objectives were listed in order to analyse the moments of continuity, discontinuity and/or a departure from traditions that arise in the development of body practices as well as to identify and analyse the relations observed in the spaces in which these traditions are transmitted. For the purpose of investigating corporal practices in traditional communities, the author decided to analyse the Pomeranian community of Alto Santa Maria, located in the municipality of Santa Maria de Jetibá in the State of Espirito Santo, Brazil. Based on a qualitative approach, this study was initiated with a review of the existing literature, followed by a field research where data were collected by the mean of open interviews and observations. The interviews were analysed in an interpretative way, seeking to learn from the subjects’ answers, and the scientific quality was ensured by their previous categorisation. The data analysis enabled to recognize, among the various aspects of cultural identity, corporal culture in relation with local corporal practices. In the community of Alto Santa Maria, they evolve in a dynamic context, in which both traditional and non-traditional practices can be observed. In this perspective, it was concluded that corporal practices like games, playful activities and dances are embodied, in the described context, simultaneously as Pomeranian practices and external practices, but that they now belong to he community’s cultural practices, leading to a dialog between them.